Elizabethkingia meningoseptica: An emerging pathogen causing septicemia in an Immunocompromised patient - Pallaavi Goel; Ekadashi Rajni; Puneet Rijhwani (Journal of Research in Clinical Medicine, 2022)
Elizabethkingia meningoseptica is a rare, gram-negative bacterium, which is known as the causing agent for hospital-acquired infections, especially in immunocompromised patients and those with indwelling devices. E. meningoseptica is resistant to the most of the antibiotics making the treatment procedure a difficult task, because of which this bacterium is considered as an emerging cause of high mortality in critically ill patients. Herein, we describe a case of E. meningoseptica causing bacteremia in a young chronic kidney disease (CKD) patient who was successfully managed with an appropriate use of suitable antimicrobials. The case highlights the importance of constant and active interaction between the clinician and the microbiologist to handle such novel organisms.